Dynamics Ionospheric Plasma Bubbles Measured by Optical Imaging System - Chapagain, Narayan P. (Journal of Institute of Science and Technology, 2015)
Deep plasma depletions during the nighttime period in the equatorial ionosphere (referred to as equatorial plasma bubbles –EPBs) can significantly affect communications and navigation systems. In this study, we present the image measurements of plasma bubble from Christmas Island (2.1°N, 157.4°W, dip latitude 2.8°N) in the central Pacific Ocean. These observations were made during September-October 1995 using a Utah State University (USU) CCD imaging system measured at ~280 km altitude. Well-defined magnetic field-aligned plasma depletions were observed for 18 nights, including strong post-midnight fossilized structures, enabling detailed measurements of their morphology and dynamics. We also estimate zonal velocity of the plasma bubbles from available images. The zonal drift velocity of the EPBs is a very important parameter for the understanding and modeling of the electrodynamics of the equatorial ionosphere and for the predictions of ionospheric irregularities. The eastward zonal drift velocities were around 90-100 m/s prior to local midnight, and decreases during the post-midnight period that persisted until dawn. Journal of Institute of Science and Technology, 2015, 20(1): 20-27